Karakteristik Bahasa Jurnalistik dan Penerapannya pada Media Cetak - Aryusmar, Aryusmar (Bina Nusantara University, 2011)
Journalistic language is one kind of language used by mass media and had different characteristic with literature, scientific or conventional language in general. In journalistic language, the journalists should write according to facts and should not include their opinion; but the writing should also include informative, persuasive, and understandable meanings as general, brief, and clear. Journalistic language is a language used in public media written by considering some characteristics in order to be easily understood by the reader in general. Therefore, this article is intended to explore those characteristics and their implementation. The result shows that there are six characteristics of Journalistic language namely: brief, dense, simple, straightforward, interesting and clear. It is also found that some printed media in Indonesia haven’t met those characteristics yet.